Analisis Faktor-faktor yang Memengaruhi Pembelian Beras SPHP Bulog di Rumah Pangan Kita Kota Semarang - Dwipuspa, An Nitta; Setiyawan, Hery; Mariyono, Joko (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Rice is the main staple food for Indonesians; therefore, its availability and affordability are crucial to maintaining food security. The government, through Perum BULOG, implements the Food Supply and Price Stabilization (SPHP) program distributed via the Rumah Pangan Kita (RPK) network. This study aims to analyze the factors influencing the purchase of BULOG’s SPHP rice at Rumah Pangan Kita in Semarang City and to describe consumer characteristics. The research was conducted at three RPK outlets, RPK Life by Grace, RPK Rizky Fajar, and RPK Kawakibi using a quantitative method with a descriptive approach. A total of 120 respondents were selected using a purposive sampling technique. Data were collected through questionnaires, interviews, and literature studies, and analyzed using multiple linear regression, validity, reliability, and normality tests, as well as F and t tests. The results showed that most respondents were female, of productive age, had a senior high school education level, worked as housewives and laborers, had 3–4 dependents, and belonged to the middle-income group. The majority purchased SPHP rice 1–3 times per month. Psychological, personal, cultural, and social factors significantly influence the purchase of BULOG’s SPHP rice. Psychological factors relate to motivation and perception, personal factors include occupation and lifestyle, cultural factors involve values and consumption habits, while social factors are influenced by family and the surrounding environment.